Cash flows and leverage adjustments - Faulkender, Michael; Flannery, Mark J.; Hankins, Kristine Watson; Smith, Jason M. (Journal of Financial Economics, 2012)
Recent research has emphasized the impact of transaction costs on firm leverage adjustments. We recognize that cashflow realizations can provide opportunities to adjust leverage at relatively low marginal cost. We find that a firm's cashflow features affect not only the leverage target, but also the speed of adjustment toward that target. Heterogeneity in adjustment speeds is driven by an economically meaningful concept: adjustment costs. Accounting for this fact produces adjustment speeds that are significantly faster than previously estimated in the literature. We also analyze how both financial constraints and market timing variables affect adjustments toward a leverage target.